Supply chain perspective and logistics of spices in Indian retail industry. (2022) - Krishnaraj, S.; Gunaseelan, Rupa; Arunmozhi, M.; Sumandiran, C.S.P.
Abstract: This paper aims to report on the results of the study of routes and the distance of travelling by spices in traditional and organized retailing from the agricultural location to the consumer. This research is largely exploratory, and interviews and surveys with players in spice supply chain are included in the instruments of analysis. In order to assess the current state of supply chain management activities, the analysis would monitor the spice routes of distributors and evaluate the "meat kilometres" they calculate. Food miles' is a relatively recent supermarket term, and the outcome of this analysis indicates that the number of food miles in integrated supermarkets has increased significantly. The change to coordinated retailing suggests broad grocery miles for spices. The time taken between any two points was not measured as well as at which spices arrived at their destination. This is the limited scope and scope of this study for further research. The aim of the study is not to identify the food kilometer factors.